Understanding Post-Graduation Decision of Caribbean International Students to Remain in the United States - Belle, Trevis; Barclay, Susan R; Bruick, Thomas; Bailey, Phillip (Journal of International Students, 2022)
We utilized Schlossberg’s transition theory (1984) as the framework for understanding how international students from the Caribbean arrive at the decision to remain within the United States after completing their highest earned degree and joining the diaspora. Using a phenomenological research design with a sample of six international students who remained within the United States after completing their highest earned degree, we examined the underlying considerations participants made during their decision-making process. Results revealed that all six participants relied on economic, political, and social considerations, which contributed to their decision to remain in the United States.